2013
DOI: 10.1097/tp.0b013e3182a203e4
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Homeostatic Proliferation and Thymopoiesis after rATG Induction Therapy in Kidney Transplant Patients

Abstract: These findings demonstrate that, in the first month after rATG therapy, cytokine-induced homeostatic proliferation is involved in T-cell repopulation of both naïve and memory T cells. At later time points, the contribution of homeostatic proliferation diminished, which explains the observed incomplete T-cell recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 36 publications
1
43
1
Order By: Relevance
“…Recent examination of the kinetics of lymphocyte depletion following rATG given as induction therapy in renal transplantation found that rATG durably depletes the T cell compartment to counts below 250 CD3 + cells/uL at six months, compared to minimal T cell depletion following basiliximab or no induction therapy. 19 In contrast to prior studies, this recent investigation found no increase in thymopoiesis ( i.e., CD31 + cells among CD4 + or CD8 + cells) one month following rATG induction. Rather, peripheral cytokine-mediated signaling by IL-7 and IL-15 via Stat5 increased in the first month following rATG therapy, particularly among memory T cell subsets.…”
Section: Pharmacologic Lymphocyte Depletion Promotes Autoimmunitycontrasting
confidence: 80%
“…Recent examination of the kinetics of lymphocyte depletion following rATG given as induction therapy in renal transplantation found that rATG durably depletes the T cell compartment to counts below 250 CD3 + cells/uL at six months, compared to minimal T cell depletion following basiliximab or no induction therapy. 19 In contrast to prior studies, this recent investigation found no increase in thymopoiesis ( i.e., CD31 + cells among CD4 + or CD8 + cells) one month following rATG induction. Rather, peripheral cytokine-mediated signaling by IL-7 and IL-15 via Stat5 increased in the first month following rATG therapy, particularly among memory T cell subsets.…”
Section: Pharmacologic Lymphocyte Depletion Promotes Autoimmunitycontrasting
confidence: 80%
“…Gurkan et al (14) reported evidence for both thymopoiesis and homeostatic proliferation contributing to immune reconstitution after rATG. More recently, Bouvy et al (15) measured the percentage of RTE at 1, 3, and 6 months after rATG and showed no effect of rATG on thymopoiesis. Several differences with our study are noteworthy.…”
Section: Discussionmentioning
confidence: 99%
“…Several differences with our study are noteworthy. The first study (14) included pediatric patients in whom thymopoiesis could be preserved; the number of patients in Bouvy et al's (15) report was limited (8 ATG and 8 basiliximab) hampering the relevance of their findings; finally, both studies (14,15) explored thymic output during the first 6 months while we studied thymic function one year after transplantation. Hence, a thymic toxicity of ATG remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The absolute numbers of the different T cell subsets were determined via Trucount staining (Becton Dickinson, Franklin Lakes, NJ), as described by Bouvy et al (22).…”
Section: T Cell Differentiation Status and Absolute Numbers Of T Cellmentioning
confidence: 99%